Observation of mesospheric wave using collocated OH airglow temperature and radar wind measurements over Indian low latitude. Issue 10 (15th November 2019) - Ghodpage, R.N.; Taori, Alok; Gurav, O.B.; Patil, P.T.; Gurubaran, S.; Siingh, Devendraa; Naniwadekar, G.P.
Abstract: We analyzed the mesospheric winds and temperature data for investigating the waves scaling from the period of few hours to several hours (and few days) based on the airglow observations at Kolhapur (16.8°N, 74.2°E, 10.6°N dip. lat.). The data presented in this study are collected using medium frequency radar and Multispectral Scanning Photometer at low latitude station Kolhapur. We scrutinized the wind and temperature relation of these waves for the observed period from January to May 2011. The data of 56 clear nights were collected and out of which 22 nights of data shows a conspicuous wavelike features. The nocturnal variability reveals the prominent wave signatures with a period which range from 7 to 12 h (h) as a dominant nocturnal wave. The presence of quasi 2.8–4 days waves with significant amplitudes is also detected. The comparison of the winds and temperatures suggests the temperature waves to be near in phase with meridional wind component and a time delayed relation with the zonal wind component.